Content and Structure in the Advice of Ibn Lyon al-Tajibi al-Andalusi(681 AH - 750 AH) - Al-Gharbawi, Israa Abdel Reda (Journal of Tikrit University for Humanities, 2024)
The jurist, scholar, and poet Abu Uthman Saad bin Abi Jaafar Ahmad bin Ibrahim bin Leon al-Tajibi, one of the leading jurists of Andalusia, who was characterized by asceticism, knowledge, and advice. He used his poetry to spread virtue and moral values ​​among members of society, considering them as human behavior, as they represent the system of Islam in general as well as its spirit. Its essence is in all its aspects. Al-Tajibi set out, based on his Islamic background, to guide his people to the highest moral ideals after many years spent serving and highlighting values ​​and morals, which gave him experience in dealing with people of different backgrounds and diversity of characteristics. He was a poet and advisor, calling for the possession of moral values ​​and triumphing over them, and urging good behavior. His poetry of advice came with the aim of directing others -in his time and after- towards the best morals and highest qualities. In order to straighten their behavior and improve their treatment, according to his vision and cultural, religious and social principles, as well as his personal experience. Based on these ideals brought by religion, Ibn Lyon bore the burden of the issues of his time and the responsibility for their consequences, through his experiences and the essence of his culture, carrying the banner of advice and guidance to refine souls. Due to the nature of the research, its specificity, and the size of the material that will be covered, we will discuss the research in two sections. The first section includes two topics: praiseworthy actions and reprehensible actions. The second section handles topics: the composition, methods of request, and the poetic image.